GUT MICROBIOME DIVERSITY IN KAZAKHSTANI WOMEN OF DIFFERENT AGE GROUPS - Kushugulova , A.R.; Kozhakhmetov , S.S.; Baiskhanova , D.M.; Tynybayeva , I.K.; Shapekova , N.L.; Kakimova , A.B.; Saduakhasova , S.A.; Shakhabayeva , G.S.; Khassenbekova , Z.R.; Nurgozhin , T.S.; Zhumadilov , Z.S. (Eurasian Journal of Applied Biotechnology, 2014)
The human gut microflora is the largest part of the whole human microbiome that includes three enterotypes. As it has been proposed to play a crucial role in health and disease it is very important to know a microbial composition of the gut microbiome. But little is known about the gut microbiome compositional structure in Kazakhstani population. We studied the gut microbiome phylogenetic composition, determined its types and compared the microbial composition of the gut microbiome in different aged Kazakhstani women. Subjects were divided into three groups: first group included six young females (to 44 years old), second group – eighteen middle-aged females (50-75 years old) and the third group – six old females (above 90 years old). For analysis of gut microbiome composition amplification of the locus 16S rRNA, transformation of high copy plasmid vectors with ligated amplified DNA fragments into competent cells, sequence-PCR and sequencing were conducted. According to the sample analysis there have been found two precise enterotypes of the gut microbiome with significant differences: in the first case prevailed Bacteroidetes type, and in the second case – Firmicutes type. It is also important to notice, that studying species diversity between groups has shown the greatest diversity in subjects of 30 to 75 years and the poorest diversity was observed in individuals of 90 years and above and detected types of gut microbiota composition depends on the age factor. More research is needed for a better understanding compositional structure of the gut microbiome of Kazakhstani population.